Extracellularly Released Calreticulin Induced by Endoplasmic Reticulum Stress Impairs Syncytialization of Cytotrophoblast Model BeWo Cells - Naoyuki Iwahashi; Midori Ikezaki; Kazuchika Nishitsuji; Madoka Yamamoto; Ibu Matsuzaki; Naoki Kato; Naoyuki Takaoka; Mana Taniguchi; Shin-ichi Murata; Kazuhiko Ino; Yoshito Ihara (Cells, 2021)
The pregnancy-specific syndrome preeclampsia is a major cause of maternal mortality throughout the world. The initial insult resulting in the development of preeclampsia is inadequate trophoblast invasion, which may lead to reduced maternal perfusion of the placenta and placental dysfunction, such as insufficient trophoblast syncytialization. Endoplasmic reticulum (ER) stress has been implicated in the pathology of preeclampsia and serves as the major risk factor. Our previous studies suggested critical roles of calreticulin (CRT), which is an ER-resident stress response protein, in extravillous trophoblast invasion and cytotrophoblast syncytialization. Here, we studied the mechanism by which ER stress exposes the placenta to the risk of preeclampsia. We found that CRT was upregulated in the serum samples, but not in the placental specimens, from preeclamptic women. By using BeWo cells, an established model of cytotrophoblasts that syncytialize in the presence of forskolin, we demonstrated that thapsigargin-induced ER stress caused extracellular release of CRT from BeWo cells and that the extracellular CRT suppressed forskolin-induced release of β-human chorionic gonadotropin and altered subcellular localization of E-cadherin, which is a key adhesion molecule associated with syncytialization. Our results together provide evidence that induction of ER stress leads to extracellular CRT release, which may contribute to placental dysfunction by suppressing cytotrophoblast syncytialization.